P.095 Novel use of fluorescein sodium in the resection of a pediatric posterior fossa tumor. (5th June 2019) - Almojuela, A; Honey, CM; Gomez, A; Hasen, M; MacDonald, C; Kazina, C; Serletis, D
Abstract : Background: Gross total resection of pediatric posterior fossa tumors is paramount towards improving progression-free survival. Fluorescein accumulates in tumoral tissue, where the blood-brain barrier is disrupted. It can therefore potentially aid in differentiating tumoral versus normal tissue. We aimed to evaluate the efficacy of fluorescent-guidance (using fluorescein) towards the resection of a pediatric cerebellar tumor, as the index case at our institution using this technique.Methods: 5 mg/kg of IV fluorescein sodium was injected upon induction of general anesthesia. During tumor resection, a yellow 560-nm filter (Kinevo microscope, Zeiss) was employed for fluorescent-guidance. The extent of resection was assessed via post-operative MRI.Results: There were no adverse side effects experienced by the patient. Tumoral material was clearly visualized under the yellow 560-nm filter, allowing for satisfactory gross total resection of the lesion (confirmed on post-operative MRI). Preliminary pathology was consistent with medulloblastoma.Conclusions: Fluorescent-guided resection of pediatric posterior fossa tumors appears to be a safe and useful adjunct for gross total resection of these lesions. To the best of our knowledge, this is the first reported case in Canada wherein IV fluorescein was used under a yellow 560-nm filter for resection of a posterior fossa medulloblastoma in a child.